Effect of sugars on post-thaw seminal characteristics of HF semen in tris bufferin absence and presence of glycerol - KUMAR, SATISH; SINGH, L P; MOHAN, GREESH; SAHNI, K L (The Indian Journal of Animal Sciences, 2013)
Post-thaw motility (PTM) and post-thaw aging motility (PTAM) were significantly (P